THE CORRELATION BETWEEN COGNITIVE STYLE AND STUDENTS' LEARNING ACHIEVEMENT ON GEOMETRY SUBJECT - Udiyono Udiyono; Muhammad Ridlo Yuwono (IKIP Siliwangi and I-MES, 2018)
The objective of the research is to identify whether there is a positive correlation between cognitive style and students' learning achievement on geometry subject. The research is classified as correlational quantitative research. The population of the research is all students of mathematics education program at Widya Dharma University in the academic year of 2015/2016. The sample is the students in semester IV B. It was taken by cluster random sampling. The instrument is a psychiatric test, GEFT and learning achievement test. The technique of data analysis is simple linear regression analysis. The result of the research is there is a positive correlation between cognitive style and students' learning achievement on geometry subject. The coefficient determination is r2 = 0.6209. It means the increase and decrease of students' learning result on geometry subject 62.09% can be explained by cognitive style with linear correlation equationÂ Å¶= -2.9650 + 4.6513X. Meanwhile, 37.91% is influenced by another factor. 13 out of 17 samples are categorized as students FD and 4 students are classified as FI. The mean score of students FD is 16 while students FI is 59.5385. It means students FI has better learning achievement than students FD on geometry subject.